Using finite strain 3D-material models in beam and shell elements - Klinkel, Sven; Govindjee, Sanjay (Engineering computations, 2002)
In this paper an interface is derived between arbitrary three-dimensional material laws and finite elements which include special stress conditions. The mechanical models of beams and shells are usually based upon zero-stress conditions. This requires a material law respecting the stress condition for each finite element formulation. Complicated materials, e.g. finite strain models are often described in the 3D-continuum. Considering the zero-stress condition requires a reformulation of these material laws, which is often complicated. The subject of this paper is to incorporate physically non-linear 3D-material laws in beam and shell elements. To this effect a local algorithm will be developed to condense an arbitrary 3D-material law with respect to the zero-stress condition. The algorithm satisfies the stress condition at each integration point on the element level.